2018
DOI: 10.20535/ibb.2018.2.4.151459
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Luminos Bacteria Photobacterium phosphoreum as a Bioindicator of Geomagnetic Activity

Abstract: Проблематика. Сучасною проблемою є визначення особливостей характеристик різних мікроорганізмів для біоіндикації активності стану геофізичних параметрів середовища. Мета. Виявлення кореляційних залежностей між значеннями інтенсивності світіння бактерій Photobacterium phosphoreum та факторами, що визначають геомагнітну активність. Методика реалізації. Визначались оптимальні параметри суспензії для досліджень інтенсивності біолюмінісценції як біоіндикатора стану геомагнітного поля. Протягом 2 місяців проводили м… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Therefore, the initial acceptance of geomagnetic disturbances by immunocytes is possible, but unlikely. Gorgo et al (2018) in recent study the monitoring of specific intensity of bacteria Photobacterium phosphoreum luminescence has been carried out for 2 months (September-October 2015) and it was compared to the daily values of activity of the geomagnetic field in the conditions of Kyїv, during the research of bioluminescence. Variation determination of the geomagnetic field was conducted from data of Space Environment Center, NOAA&U.S. Air Force.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the initial acceptance of geomagnetic disturbances by immunocytes is possible, but unlikely. Gorgo et al (2018) in recent study the monitoring of specific intensity of bacteria Photobacterium phosphoreum luminescence has been carried out for 2 months (September-October 2015) and it was compared to the daily values of activity of the geomagnetic field in the conditions of Kyїv, during the research of bioluminescence. Variation determination of the geomagnetic field was conducted from data of Space Environment Center, NOAA&U.S. Air Force.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the average values of Ap-indexes were close to those in our observations (in September 13,7±2,68 nT; in October 14,9±1,90 nT). Surprising is the proximity of the force of influence of the intensity of variations of the magnetic field on the day of testing (Ap0) both on the manifestation of bacterial activity (Gorgo et al, 2018) and phagocytic function of neutrophils against bacteria . This, in our opinion, confirms the direct effect of the geomagnetic field disturbances on human neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that in the case of an increase in the intensity of variations of the geomagnetic field, there is a decrease in the values of the specific intensity of the bioluminescence of bacteria. The use of an automated system for monitoring the intensity of glow of luminescent bacteria makes it possible to predict in time the presence of perturbations of the magnetic field of the Earth [64].…”
Section: Criterion 3 -Bioluminescence and Color Changes Bioluminescementioning
confidence: 99%